The Period of Mafqud According to Hukum Syara’ and the Sharia Law Act in Brunei Darussalam - Nor Sabrina binti Ratna; Mas Nooraini binti Haji Mohiddin (JOURNAL OF ISLAMIC AND LAW STUDIES, 2024)
A mafqud is a person who has been missing from their original location for a long period, during which news about them has ceased, and their whereabouts are unknown. The occurrence of a mafqud leads to several issues, especially in managing property and the status of the abandoned wife. This is because, if it is proven that the mafqud has passed away, their heirs are entitled to inherit their property according to the distribution of faraidh according to hukum syara’, and it also allows the wife of the mafqud to remarry. Therefore, this study aims to explore the period of mafqud according to hukum syara’, along with the implementation of the act that has been enacted by Sharia legislation in Brunei Darussalam. The research methodology employed is descriptive qualitative, using content analysis as the analytical method. The analysis is conducted by examining secondary data, particularly legal acts, writings, journals, and articles. Additionally, library methods are used, sourcing from Islamic jurisprudence books, seminar papers, and reputable websites. According to the findings, the implementation of Brunei's Sharia law does not specify the period for managing the property of a mafqud, but only states the period for the wife believed to have been abandoned by her mafqud husband to remarry. Scholars unanimously state that the period of mafqud is based on the ijtihad (juridical reasoning) of the judge. The effectiveness of the implementation of the law, especially Sharia law, plays a crucial role in enhancing the development of mafqud management in Brunei Darussalam based on Islamic legal principles.